Outcome after surgical resection of multiple recurrent retroperitoneal soft tissue sarcoma - Willis, Franziska; Musa, Julian; Schimmack, Simon; Hinz, Ulf; Mechtersheimer, Gunhild; Uhl, Matthias; Schmidt, Thomas; Fröhling, Stefan; Büchler, Markus W.; Schneider, Martin (European journal of surgical oncology, 2021)
Introduction - Local recurrences (LR) and distant metastases (DM) are common in retroperitoneal soft tissue sarcoma (RPS). Longer time to recurrence and resection of the recurrent lesion have been identified as beneficial prognostic factors for overall survival (OS) upon first tumor relapse. However, prognostic factors concerning OS upon subsequent recurrences are scarcely defined. In this study, we aimed to identify prognostic factors for post-relapse outcome in multiple recurrent RPS. - Methods - Patients undergoing resection of primary and recurrent RPS at the University Hospital Heidelberg were retrospectively analyzed. Multivariable Cox regression analyses were performed to identify predictors of overall, LR- and DM-free survival. Subgroup analyses were performed for liposarcoma and leiomyosarcoma patients. - Results - 201 patients with primary disease, 101 patients with first, 66 patients with second and 43 patients with third LR as well as 75 patients with DM were analyzed. More than 12 months to recurrence and resection of recurrence were associated with improved OS after resection of first and second LR (5-year OS for first/second LR; resection: 64%/62%, no resection: 20%/46%). Gross macroscopic incomplete resection of first (p < 0.001), second (p = 0.001), and third recurrences (p < 0.001) was an independent prognostic factor for poor OS. - Conclusion - Development of LR and DM is frequent in RPS. Once a tumor relapsed, patients benefit from tumor resection not only in case of first, but also in case of subsequent recurrences.